Victorian demons : medicine, masculinity and the Gothic at the fin-de-siècle - Smith, Andrew, 1964- (Manchester University Press, 2017)
Victorian demons provides the first extensive exploration of largely middle-class masculinities in crisis at the fin de siècle. It analyses how ostensibly controlling models of masculinity became demonised in a variety of literary and medical contexts, revealing the period to be much more ideologically complex than has hitherto been understood, and makes a significant contribution to Gothic scholarship.Andrew Smith demonstrates how a Gothic language of monstrosity, drawn from narratives such as 'The Strange Case of Dr Jekyll and Mr Hyde' and 'Dracula', increasingly influenced a range of medical and cultural contexts, destabilising these apparently dominant masculine scripts. He provides a coherent analysis of a range of examples relating to masculinity drawn from literary, medical, legal and sociological contexts, including Joseph Merrick ('The Elephant Man'), the Whitechapel murders of 1888, Sherlock Holmes's London, the writings and trials of Oscar Wilde, theories of degeneration and medical textbooks on syphilis.
Keywords: English literature -- 19th century -- History and criticism.; Medicine in literature.; Literature and medicine -- Great Britain -- History -- 19th century.; Gothic revival (Literature) -- Great Britain.; Masculinity in literature.; Demonology in literature.; Diseases in literature.; Men in literature.; Diseases.; Gender identity.; Medicine -- History.; Men.; Gothic fiction (Literary genre) -- Great Britain.; Disease; Medicine in Literature; Gender Identity; History of Medicine; History, 19th Century; Men; United Kingdom; Littérature anglaise -- 19e siècle -- Histoire et critique.; Médecine dans la littérature.; Littérature et médecine -- Grande-Bretagne -- Histoire -- 19e siècle.; Roman gothique -- Grande-Bretagne.; Masculinité dans la littérature.; Démonologie dans la littérature.; Maladies dans la littérature.; Hommes dans la littérature.; Littérature frénétique -- Grande-Bretagne.; Identité de genre.; Médecine -- Histoire.; Médecine -- Histoire -- 19e siècle.; Maladies.; Hommes.; sex role.; history of medicine.; men (male humans); Literature.; Literary Theory.; LITERARY COLLECTIONS -- European -- English, Irish, Scottish, Welsh.; LITERARY COLLECTIONS / European / English, Irish, Scottish, Welsh; Medicine; Gothic fiction (Literary genre); Gender identity; Diseases; Demonology in literature; Diseases in literature; English literature; Gothic revival (Literature); Literature and medicine; Masculinity in literature; Medicine in literature; Men in literature; Great Britain; Englisch; Krankheit -- Motiv; Literatur; Männlichkeit -- Motiv; Mannelijkheid.; Medische aspecten.; Culturele aspecten.; Gothic novel.; Victoriaanse tijd.; Englisch.; Anthologies -- general -- Literary theory.; 1800-1899; Criticism, interpretation, etc.; History